Systematic Literature Review on The Use of Electronic Prescribing (E-Prescribing) At Hospital Installation - Dwi Lestari, Rinna; Sundari, Sri; Trisnadi, Setyo (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The service quality of hospitals is a benchmark for the success of health sector development. The use of electronic prescribing (E-prescribing) enables a faster, more accurate, and more efficient service process in hospitals. Related to this matter, current research was carried out aim-ing to examine the use of E-prescribing in the medical sector, especial-ly in hospitals. This study encompassed three phases: (1) identification of relevant literature and data collection; (2) analysis and assessment of the identified literature; and (3) additional categorization of the ob-tained literature. The results of this study concluded that the use of e-prescribing can improve the service quality received by patients in hos-pitals. In addition, its use can also reduce the prescribing errors and increase the cost and time efficiency. However, medical errors are still found, in which it is primarily affected human factors (human error). On the other hand, patient information data must be kept protected, yet the use of e-prescribing can cause the prescription data which is part of confidential medical records and should be protected to be easily ac-cessed by irresponsible parties.